Reconstruction of Traumatic Defect of the Lower Third of the Leg Using a Combined Therapy: Negative Pressure Wound Therapy, Acellular Dermal Matrix, and Skin Graft - Sergio Brongo; Domenico Pagliara; Nicola Campitiello; Corrado Rubino (Case Reports in Surgery)
The reconstruction of lower third of the leg is one of the most challenging problems for plastic and reconstructive surgeons and current approaches are still disappointing. We show an easy option to obtain a coverage of traumatic pretibial defects with good aesthetic and functional results: the association of negative pressure wound therapy, acellular dermal matrix, and skin graft. The choice of this combined therapy avoids other surgical procedures such as local perforator flaps and free flaps that require more operating time, special equipment, and adequate training.